2017
DOI: 10.1155/2017/3609062
|View full text |Cite
|
Sign up to set email alerts
|

Shape Optimization of Bone-Bonding Subperiosteal Devices with Finite Element Analysis

Abstract: Subperiosteal bone-bonding devices have been proposed for less invasive treatments in orthodontics. The device is osseointegrated onto a bone surface without fixation screws and is expected to rapidly attain a bone-bonding strength that successfully meets clinical performance. Hence, the device's optimum shape for rapid and strong bone bonding was examined in this study by finite element analyses. First, a stress analysis was performed for a circular rod device with an orthodontic force parallel to the bone su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Among various attempts to overcome this difficulty, FE analysis has been commonly utilized. FE analysis is a numerical method that calculates the stresses and determines the mechanical behavior of complex structures [26]. Recently, the predictability of FE analysis in orthodontic treatment has been validated by evaluation with clinical feedbacks [27].…”
Section: Discussionmentioning
confidence: 99%
“…Among various attempts to overcome this difficulty, FE analysis has been commonly utilized. FE analysis is a numerical method that calculates the stresses and determines the mechanical behavior of complex structures [26]. Recently, the predictability of FE analysis in orthodontic treatment has been validated by evaluation with clinical feedbacks [27].…”
Section: Discussionmentioning
confidence: 99%
“…Semicircular onplants were also tested and they have proved to have greater strength than circular onplants [22]. Ogasawara et al performed a finite element analysis to determine the shape optimization of the subperiosteal devices; the study group concluded that a rectangular cross-section is the most mechanically favorable to guarantee higher resistance to bonding strength in simulated rat calvarium bone [24].…”
Section: Biomechanical Propertiesmentioning
confidence: 99%